Implementation of Intelligent Green Energy Management System - Yang, Chao-Tung; Yan, Yin-Zhen; Shen, Yu-Chuan; Wang, Yun-Ting; Huang, Chao-Wei; Chen, Shuo-Tsung (International Journal of Informatics and Information Systems, 2018)
In this work, we mainly apply the cloud infrastructure (IaaS) and virtualization technology to provide the construction services of a green energy management system. First of all, we used MySQL Cluster database technology to build a data storage system which can solve the challenge of large demand. Digital electricity meter data and environmental information are collected efficiently and quickly in the proposed green energy management system. Next, a virtualized user-interface is provided by graphical presentation to facilitate data analysis. Finally, we control the electricity equipment to reduce Power Usage Effectiveness (PUE) and the overall power consumption target-based on this virtualized user-interface of the data analysis.